Integrable Stochastic Dualities and the Deformed Knizhnik–Zamolodchikov Equation. (13th August 2018) - Chen, Zeying; de Gier, Jan; Wheeler, Michael
Abstract: We present a new method for obtaining duality functions in multi-species asymmetric exclusion processes (mASEP), from solutions of the deformed Knizhnik–Zamolodchikov (KZ) equations. Our method reproduces, as a special case, duality functions for the self-dual single species ASEP on the integer lattice.